The Intersection of Migration, Multiculturalism, and Social Media: A Systematic Review - Mirafshari, Seyyed Mohammad (Journal of Posthumanism, 2025)
The current systematic review approaches the role of social media in migration and multiculturalism. It specifically addresses the question how migration and cross-cultural relations are affected by technologies and their platforms. Using the PRISMA method and the PICOS approach, we searched for literature on the specified research area on Scopus and Web of Science and finally accessed 44 studies on the topic. The following results were reported as the seven major themes: Impact of Social Media on Migration Discourses, Social Integration and Social Networks, Digital Tools and Cultural Preservation, Ethnic Identity and Acculturation, Role of Media in Multiculturalism, Transnational Communication and Community, and Youth and Digital Media and Migration. These themes mention the role of social media in the decision-making processes of migrants, integration processes of migrants, and views of the wider society on multiculturalism. In addition, the results demonstrate the paradoxical function of social media in enabling engagement while reproducing underlying social problems, which can be useful in the area of policies, teaching, and the media in the use of technology towards promoting multiculturalism in migration.